Temporal analysis of the follow-up of children with early congenital syphilis in a philanthropic hospital in northeastern Brazil from 2010 to 2020 (Research, Society and Development, 2023)
Congenital syphilis (CS) is one of the most serious preventable adverse outcomes of pregnancy. The objective of this study was to carry out a descriptive temporal analysis of the follow-up of children with early CS in northeastern Brazil between 2010 and 2020. Study carried out in a Philanthropic Maternity Hospital in Aracaju SE, between 2010 and 2020 (subdivided into 2010-2014 | 2015-2020) through analysis of physical records of newborns (NB) with CS. In both periods, most mothers, multiparous (56.3% | 92.2%), with no history of abortion (63.7% | 76.5%) were adequately treated (72.2% | 75.5% ) with negative VDRL (90.2% | 100%). Between 2015 and 2020, there was an improvement in the level of maternal education (48.8%), prenatal care (58.4%) and adherence to partner treatment (44.1%) compared to the previous period. As for the newborns, in both periods the majority had a birth weight greater than 2500g (84.4% | 90.3%), positive VDRL in peripheral blood (70.4% | 76.7%) and non-reactive in the CSF ( 2.2% | 2.2%); in both periods, it was also evidenced that a minority had alterations in the hearing screening (1.1% | 5.4%) and fundoscopy (1.1% | 0.6%), but on long bone radiography between 2010-2014, 8 .5% changed and between 2015-2020 there was an increase to 47.3%. It is concluded that the expansion and improvement of prenatal care, development and improvement of diagnostic and therapeutic technologies, have the power to make CS control an ever closer scenario.